FLUOROSENSOR OF Hg2+ AND Cu2+ HEAVY METAL IONS FROM COMPLEX COMPOUND OF Co2+ AND para-di-2-(1-phenyl-3-pyridyl-4,5-dihydro-1H-pyrazole-5-yl)benzene LIGAND - Yulian Syahputri; Linda Jati Kusumawardani (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
Industrial activities like waste disposals and domestic activities may produce wastes in form of heavy metal like Hg2+ and Cu2+. The purpose of this research is to synthesize the complex compound of metal ion Co2+ and para-di-2-(1-phenyl-3-pyridyl-4,5-dihydro-1H-pyrazole-5-il)benzene ligand and its potentials as the fluorosensor of Hg2+ and Cu2+ heavy metal ions. Complex compounds are characterized with fourier-transform infrared (FTIR), ultraviolet-visible (UV-Vis) spectrophotometer, and spectrofluorometer. After that, complex compound fluorosensor study is conducted by adding Hg2+ and Cu2+ heavy metal ions using spectrofluorometer. The results show that the synthesis of complex compound generates brownish yellow sediment with the yield of 36% and melting point of 243.2oC. The result of characterization with FTIR (KBr, cm-1) generates 3060.65 (C-H aromatic), 2851-2919.46 (C-H pyridine), 2363.23 and 1640.14 (C=N), 1493.24-1594.5 (C=C), and 1326.38-1019.74 (C-N). The result of ultraviolet-visible spectrophotometer scanning obtains two absorption peaks on 250 nm and 366 nm in the concentration of 5x10-5 M with the respective molar absorptivity of log Ɛ 4.44 and log Ɛ 4.23. High molar absorptivity value shows that the complex compound has high fluorescence intensity. It is proven with the generation of emission fluorescence intensity of 1150 a.u. at the wavelength of 470 nm. The study of complex compound fluorescence in the addition of Hg2+ and Cu2+ heavy metal ions with spectrofluorometer shows that the complex compound in the addition of Hg2+ heavy metal ion can be made as fluorosensor with turn-on type while the complex compound in the addition of Cu2+ heavy metal ion can be made as fluorosensor with turn-off type.